2020
DOI: 10.1186/s12978-020-00942-7
|View full text |Cite
|
Sign up to set email alerts
|

Women’s and girls’ experiences of reproductive coercion and opportunities for intervention in family planning clinics in Nairobi, Kenya: a qualitative study

Abstract: Background: Reproductive coercion (RC), which includes contraceptive sabotage and pregnancy coercion, may help explain known associations between intimate partner violence (IPV) and poor reproductive health outcomes, such as unintended pregnancy. In Kenya, where 40% of ever-married women report IPV and 35% of ever-pregnant women report unintended pregnancy, these experiences are pervasive and co-occurring, yet little research exists on RC experiences among women and adolescent girls. This study seeks to qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…More than 1 in 3 (36%) women report currently using a modern form of contraception [31]. Although no previous quantitative studies of RC have been conducted in Kenya, our qualitative formative research among women and girls seeking contraceptive services suggested that RC and IPV are highly prevalent in this context, and that RC appears to pose a major barrier to successful contraceptive use [32].…”
Section: Kenyan Country Contextmentioning
confidence: 80%
See 1 more Smart Citation
“…More than 1 in 3 (36%) women report currently using a modern form of contraception [31]. Although no previous quantitative studies of RC have been conducted in Kenya, our qualitative formative research among women and girls seeking contraceptive services suggested that RC and IPV are highly prevalent in this context, and that RC appears to pose a major barrier to successful contraceptive use [32].…”
Section: Kenyan Country Contextmentioning
confidence: 80%
“…Semi-structured interviews with contraceptive service providers and clinic managers were conducted to understand providers' experiences with patients reporting RC and IPV, and to identify further areas for adaptation and integration. Detailed methods and findings for this qualitative study are reported elsewhere [32].…”
Section: Description Of Intervention Adapting Arches To the Kenyan Comentioning
confidence: 99%
“…Similar to many other LMIC contexts, unintended pregnancy is high in Kenya, with 25.4% of births being mistimed and 10.3% unwanted (25), and the more than 2 in 5 women reporting IPV in the country are at 70% increased odds of unintended pregnancy as compared to their same age peers (26). More than 1 in 3 (36%) women reporting currently usinga modern form of contraception (26).Although no previous quantitative studies of RC have been conducted in Kenya, our qualitative formative research among women and girls seeking contraceptiveservicessuggested that RC and IPV are highly prevalentin this context, and that RC appears to pose a major barrier to successful contraceptive use (27).…”
Section: Kenyan Country Contextmentioning
confidence: 84%
“…Semistructured interviews with contraceptive service providers and clinic managers were conducted to understand providers' experiences with patients reportingRC and IPV, and to identify further areas for adaptation and integration. Detailed methods and findings for this qualitative study are reported elsewhere (27).…”
Section: Adapting Arches To the Kenyan Contextmentioning
confidence: 99%
See 1 more Smart Citation